Ibrutinib as a promising treatment for pulmonary complications due to refractory chronic graft versus host disease - İlhan, Osman; Cengiz Seval, Güldane; Uzay, Ant; Kaya, Emin; Öztürk, Zübeyde Nur; Deveci, Burak; Yavaşoğlu, İrfan; Ural, Ali Uğur; Beköz, Hüseyin Saffet; Ayli, Meltem; Sevindik, Ömür Gökmen; Civriz Bozdağ, Sinem; et al. (Elsevier Science Inc, 2020)
Introduction: Despite major improvements in allogeneic hematopoetic stem cell transplantation form matched related/ unrelated donor over last decades, chronic graft-versus-host disease (cGVHD) is still the leading cause of late treatmentrelated deaths among recipients. Ibrutinib is a first class inhibitor of BTK was recently employed in corticosteroid-refractory chronic GVHD with encouraging overall response rates Herein, we share a real-life experience using ibrutinib in the treatment of steroid-refractory cGVHD. Patients and Methods This multicenter retrospective study conducted in 10 different stem cell transplant centers included 44 adult patients diagnosed with steroid-refractory cGVHD. We treated off-label these patients from June 2017 to July 2019 with ibrutinib with a dose of 420 mg. Organ sites affected and cGVHD grading were classified according to the NIH 2014 criteria. Results Patients had undergone both myeloablative and non-myeloablative Allo-SCT for a variety of underlying hematological malignancies. As expected mouth and skin were the most frequently involved organs and 67 % of patients showed evidence of cGVHD in more than two organs. The median Karnofsky Performance Status score was 65%. At a median follow-up of 22.3 months (range 7.1-109 months) after evidence of cGVHD showed, 36 (81.8%) patients were still receiving ibrutinib and 4 (9.1%) had discontinued treatment, because of cGVHD progression. Treatment duration ranged from 2 to 12 months (median 6 months) for all patients. Only three patients had grade 2 muscle spasm, arrhythmia and diarrhea as adverse events and need to reduce the 25% of drug dosage. No several adverse events due to ibrutinib were observed in our cohort. In the all treated population, based on the 2005 NIH cGVHD Consensus Panel response criteria, 45.5% PR and 20.5% CR were achieved. Six patients had progression on manifestations of cGVHD. For the responders, the median time to initial response was 28 days. Nine patients had stable disease under the ibrutinib treatment and still continue receiving. Analysis by organ domain showed similar rates of response in the lung (76.4%) skin (66.7%), and GIS (57.1%). However the response in the liver (54.2%) was lower than the others. Out of 17 patients with bronchiolitis obliterans as a manifestation of cGVHD, we observed an immediate improvement in stability of FEV1 decline that persisted over the study period despite the decreased steroid dosing in 13 patients, 3 patients had stable FEV1 and only 1 patient had reduction in FEV1. Discussion Our study suggests that ibrutinib is a safe and effective agent that reduces steroid requirements and stabilizes lung function in patients with bronchiolitis obliterans as a manifestation of cGVHD. Our study adds to a growing body of evidence for ibrutinib's use in cGVHD. It is important to note that, larger prospective studies are needed to verify and augment our findings.
Keywords: Promising Treatment; Pulmonary Complications; Refractory Chronic